The Foreign Service during the National Organization of the Argentine Republic through the diplomatic career of Manuel Rafael García (1860-1880) (Res Gesta, 2021)
The article recovers a good part of the diplomatic career of Manuel Rafael García. It reveals the personal and political expectations of the actor -identified with the liberal nationalist sector of Buenos Aires in the mid-1850s, and his relations with the Confederation leaderships, in his access to the Foreign Service. It addresses the broad framework of action revealed by the diplomat in office prior to the 1868 presidential replacement and aims to offer a greater understanding of the historical process and some of the early-stage functions of that state level.
Keywords: State; Foreign Relations; Foreign Service; Diplomats